Table of contents and editorial information for Vol. 8, no. 3, Spring 1981. - Jerry L. Jinks (Educational Considerations, 1981)
Table of contents and editorial information for Vol. 8, no. [3], Spring 1981. [This issue mislabeled as vol. 8, no. 2.]